Pollution, Climate Change, and their MPACT in Cardiovascular and Respiratory Diseases - González, Alcibey Alvarado (European Journal of Applied Sciences, 2024)
The effects of climate change and pollution are widespread and rapidly intensifying and are largely driven by greenhouse-gas (GHG) emissions from burning fossil fuels. Global mean temperatures have already increased by 1.1°C since 1900, and given the current policies and actions, a warming of 2.5°C to 2.9°C or more by the end of this century is expected. Most of the change having occurred in the past 50 years. The climate change is happening faster than expected and that the window to act is quickly closing. The severe injuries induced by pollution and climate change affect the morbidity and mortality of the planet and the species that inhabit it. The human species has the tools and knowledge to reduce this injury and safeguard the future of a habitable planet. One of the great stumbling blocks to achieve this end are the political and economic interests of a sector of the same species that has enough power and control to stop the healthy tools that could solve a problem that is planetary. This document concisely discusses climate change and pollution as etiologies of diseases, giving special emphasis to cardiovascular and respiratory diseases, which constitute a significant example of them but are obviously not the only ones.